Number and size of acquired melanocytic nevi and affecting risk factors in cases admitted to the dermatology clinic - İyidal, Ayşegül Yalçınkaya; Gül, Ülker; Kılıç, Arzu (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: The size and number of acquired melanocytic nevi (AMN) and presence of dysplastic nevi are the leading risk factors that should be recognized in the development of malignant melanoma. Aim: To evaluate AMN and risk factors in the development of AMN in all age groups admitted to a dermatology outpatient clinic. Material and methods : Four hundred and twelve patients who were admitted to the dermatology outpatient clinic for any dermatological symptom and who accepted to participate in the study were randomly included in the study. For each case, background-family history and dermatological findings were recorded. All AMN observed in the patients were dermatoscopically examined. Results : The presence of more than 50 nevi was significantly higher in males, in individuals who had a history of sunburn and smokers. The number of nevi that were 5 mm and below was found to be higher in individuals who regularly sunbathed their face/body, in individuals using sunscreen, in individuals who had a history of sunburn, smokers and alcohol users. The number of nevi that were above 5 mm was higher in smokers. The total dermatoscopy score between 4.75 and 5.45 was found to be higher in individuals who had more than 50 nevi, in individuals exposed to more than one chemical substance and in alcohol users. Conclusions : When determining the patient’s risk factors, factors such as the patient’s sunbathing habits and chemical substance exposure features should be taken into consideration besides the number and size of nevi.